RURAL TOURISM, A NEW ALTERNATIVE FOR THE SOUTH OF ALBANIA - Xarba, Belinda Meshini; Shehu, Hidajet (European Scientific Journal, ESJ, 2014)
Structural changes in economies are causing severe stress in many rural areas especially for those with a high dependence on agriculture. Such areas exist in most countries in Europe here farm revenue is decreasing. Policy makers and local leaders are searching to find innovative ways in order to resolve the economic problems of these areas. The EU in an effort to resolve the problems that the rural areas are facing, has developed a framework of support of rural integrated development. By doing so it promotes policies that enforces the development of new economic activities in rural areas, among which agritourism occupies an important position. The article analyse in principe rural tourism and agritourism role and the new opportunities for agriculture. In the context of the need for new solutions to the environmental crisis and the global crisis on development, new social demands on rural spaces have inevitably conduced to the design of new policies that modify the rural status by means of territorial control, environmental impact assessment, conservation strategies, management plans etc. This article proposes to look at how agritourism and rural tourism can contribute to the development of the countryside. More precisely the article focuses on three main aspects: (a) Rural tourism through its functions as a mean of local development, (b) Agritourism through its functions as a mean of local development and (c) The Antigone actual situations of agritourism and rural tourism in specific.